Copper-clad plate, resin composition for copper-clad plate, spherical silicon and preparation process of spherical silicon

By using spherical silicon composed of spherical silica and in-situ synthesized zinc molybdate particles as fillers in the copper clad plate, the problems of severe wear and low spherical silicon filling during drilling of copper clad plates in the prior art are solved. Achieve higher fill volume and better machining performance.

CN119490697APending Publication Date: 2025-02-21SUZHOU GINET NEW MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411609442.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing copper clad plates have severe wear during drilling and the ball silicon filling volume is low, which affects the processing performance.

Method used

Spherical silicon composed of spherical silica and zinc molybdate particles growing diffusely on its surface as filler, and zinc molybdate particles are synthesized in situ on the surface of spherical silica by hydrothermal method to optimize their distribution and binding. sex.

Benefits of technology

It effectively improves the drilling processing performance of copper clad plate, reduces drill bit wear, increases the filling amount of ball silicon, and enhances the compatibility of filler and resin, improves the peel strength of copper clad plate and reduces dielectric loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490697A_ABST
    Figure CN119490697A_ABST
Patent Text Reader

Abstract

The invention discloses a copper-clad plate, a resin composition for the copper-clad plate, spherical silicon and a preparation process of the spherical silicon, and belongs to the technical field of copper-clad plates. The spherical silicon is composed of spherical silicon dioxide and zinc molybdate particles growing on the surface of the spherical silicon dioxide in an in-situ dispersion mode, the diameter of the spherical silicon dioxide is smaller than 10 micrometers, D50 ranges from 0.6 micrometer to 6 micrometers, the content of zinc molybdate in the unit area of the surface of the spherical silicon dioxide is 0.03 g / m < 2 > to 1 g / m < 2 >, and the size of the zinc molybdate particles is smaller than or equal to 400 nm. The preparation process comprises the following steps: contacting / mixing spherical silicon dioxide with soluble molybdate and zinc salt in a water-based reaction system; and carrying out in-situ reaction on soluble molybdate and zinc salt on the surface of the spherical silicon dioxide to form spherical silicon chemically coated with zinc molybdate particles. According to the method, the zinc molybdate is directly synthesized on the surface of the spherical silicon dioxide in situ through a hydrothermal method, so that the structural morphology of the obtained spherical silicon and the size of zinc molybdate particles can be effectively controlled, and further it is guaranteed that drill bit abrasion is effectively improved when the copper-clad plate is drilled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper-clad laminates and fillers for copper-clad laminates, and more specifically, relates to a copper-clad laminate, a resin composition for copper-clad laminates, spherical silicon and a preparation process thereof. Background Art

[0002] Copper clad laminate is a plate-like material made by impregnating electronic fiberglass cloth or other reinforcing materials into resin, covering one or both sides with copper foil and hot pressing. It is called copper clad laminate, or copper clad laminate for short. The performance of copper clad laminate basically determines the quality, performance, manufacturing level, manufacturing cost, and long-term reliability and stability of printed circuit boards.

[0003] In recent years, electronic products have tended to develop in a sophisticated and multifunctional direction. The processing technology of copper clad laminates has become more complicated. In order to reduce the thermal expansion coefficient of the material, more and more fillers are added. PCB processing requires drilling. At the same time, since the fillers are generally hard, the high-filled fillers cause the drill bit to wear faster, making the drilling process more difficult and the cost increased. At present, the main method to reduce the wear of drilling drills on the market is to add fillers such as talcum powder and aluminum hydroxide. However, talcum powder has a flaky structure and a large specific surface area, which leads to high viscosity of the glue and cannot be applied to high-filler filling systems. Aluminum hydroxide will release water when heated at around 200°C, which is easy to cause board explosion.

[0004] Zinc molybdate material is a good lubricating material, which has the characteristics of not decomposing at high temperature and not containing crystal water, so it has been studied to apply it to printed circuit boards. For example, the application case of Chinese patent application No. 2015110289065 discloses a thermosetting resin composition and a prepreg, a laminate and a circuit carrier containing it, and it discloses that a composition of zinc molybdate or ammonium molybdate and silicon dioxide can be used as an inorganic filler of the thermosetting resin composition, thereby improving the drilling processing performance of the laminate to a certain extent. However, if zinc molybdate is added directly, in order to achieve a better lubrication effect, adding a small-sized zinc molybdate is the best effect due to the good dispersibility of small particles, but adding a small-sized zinc molybdate will result in high viscosity and insufficient addition, and a large-sized zinc molybdate is difficult to disperse in the material, resulting in a small lubrication effect on the drill bit during drilling. At the same time, zinc molybdate is a weakly ionized material, and its ionization will produce molybdate ions and zinc ions. Excessive amounts of these ions will cause the copper clad laminate to have poor resistance to ion migration, and ultimately cause the copper clad laminate to fail.

[0005] For another example, Chinese patent application No. 2022800372276 discloses a supported zinc dimolybdate hydroxide / silicon dioxide composite and its use in a polymer formulation, wherein the preparation process comprises: reacting a zinc compound (such as zinc oxide) and molybdenum trioxide in an aqueous system to form a reaction mixture, and contacting the reaction mixture with silicon dioxide to form a supported zinc dimolybdate hydroxide / silicon dioxide composite, wherein at least 80% by weight of the zinc dimolybdate hydroxide in the obtained supported zinc dimolybdate hydroxide / silicon dioxide composite is in the form of Zn 3 Mo 2 O 8 (OH) 2 The patent uses MoO 3 The method of reacting with zinc compounds, MoO 3 It is a solid substance that is difficult to dissolve in water. The synthesized zinc molybdate will contain unreacted molybdenum oxide, which will weaken its effect in reducing drill wear. At the same time, molybdenum trioxide is a semiconductor material with poor insulation. The presence of unreacted molybdenum oxide will also make the copper clad laminate have poor insulation.

[0006] In addition, the development of high-speed copper clad laminates has made copper clad laminates thinner and thinner. If the size of the filler is too large, protrusions will form on the surface of the copper clad laminate, and it may also affect the copper clad laminate processing equipment. Therefore, the size of the filler needs to be strictly controlled. Summary of the invention

[0007] The first object of the present invention is to provide a spherical silicon for copper clad laminates, the spherical silicon comprising spherical silicon dioxide and zinc molybdate particles dispersed and grown in situ on the surface of the spherical silicon dioxide, so as to solve the problem that when the existing spherical silicon products are added to the copper clad laminates, the drilling processing performance of the copper clad laminates is relatively poor and the filling amount of the spherical silicon is relatively low;

[0008] The second object of the present invention is to provide a modified spherical silica for copper clad laminates, by further modifying the spherical silica chemically coated with zinc molybdate particles, so as to further improve the compatibility between the spherical silica filler and the resin, and effectively control the hydroxyl content on the surface of the spherical silica;

[0009] The third object of the present invention is to provide a copper-clad laminate or a resin composition for a copper-clad laminate using the above-mentioned spherical silica or modified spherical silica as a filler, thereby effectively improving the drilling performance of the copper-clad laminate;

[0010] The fourth object of the present invention is to provide a preparation process of the above-mentioned spherical silicon or modified spherical silicon.

[0011] In order to achieve the above object, the technical solution provided by the present invention is:

[0012] The first aspect of the present invention provides spherical silicon for copper-clad laminates, which is composed of spherical silicon dioxide and zinc molybdate particles in-situ dispersedly grown on the surface of the spherical silicon dioxide, with a diameter of less than 10 microns, a D50 of 0.6 to 6 microns, and a size of the zinc molybdate particles on the surface of the spherical silicon dioxide of ≤400nm.

[0013] The spherical silicon of the present invention is composed of spherical silicon dioxide and zinc molybdate particles dispersedly grown in situ on the surface of the spherical silicon dioxide. On the one hand, it can effectively solve the technical problem in the prior art that the improvement effect on the drilling wear resistance of the copper clad laminate when silicon dioxide is directly and physically mixed with zinc molybdate is limited, and the viscosity of the material will not be affected. On the other hand, because the zinc molybdate particles are chemically grown in situ on the surface of the spherical silicon dioxide, the combination of the zinc molybdate and the silicon dioxide is relatively firm and is not easy to fall off.

[0014] It should also be noted that the distribution of zinc molybdate particles on the surface of spherical silicon dioxide has an important influence on the application effect of spherical silicon in copper-clad laminates. The size of zinc molybdate particles in the present invention is ≤400nm, and the zinc molybdate content per unit area on the surface of spherical silicon dioxide is 0.03-1g / m 2 The zinc molybdate particles are highly dispersed on the surface of the spherical silicon dioxide, which can ensure that the drilling performance of the copper clad laminate can be effectively improved when the spherical silicon is applied to the copper clad laminate, while also not causing adverse effects on other application performance parameters of the copper clad laminate such as the peel strength.

[0015] Furthermore, the pH of the spherical silica is 6-8, and the D50 of the spherical silica is 0.5-5 microns.

[0016] The second aspect of the present invention provides a process for preparing spherical silicon for copper-clad laminates, comprising:

[0017] contacting / mixing spherical silica with soluble molybdate and zinc salt in an aqueous reaction system;

[0018] A soluble molybdate and a zinc salt are reacted in situ on the surface of spherical silicon dioxide to form spherical silicon dioxide chemically coated with zinc molybdate particles;

[0019] The soluble molybdate and the zinc salt are reacted in situ on the surface of spherical silica, and the reaction conditions include: reaction temperature of 130-180° C., reaction pressure of 1-8 MPa, and reaction time of 1-8 hours.

[0020] The present invention adopts a hydrothermal method and optimizes and controls its specific process parameters, so that highly dispersed zinc molybdate particles can be directly synthesized in situ on the surface of spherical silicon dioxide to obtain spherical silicon in which zinc molybdate particles and spherical silicon dioxide are chemically combined. The spherical silicon is applied to copper-clad laminates, which can be highly filled and can effectively reduce drill bit wear during drilling without affecting the viscosity of the material. At the same time, the combination between zinc molybdate particles and silicon dioxide in the spherical silicon prepared by the present invention is relatively strong, and it is not easy to fall off during subsequent processing. In addition, it is difficult to ensure the precise control of material size whether it is grading or screening on the market. The present invention can accurately control the content of large particles in the obtained spherical silicon product through hydrothermal synthesis, so that the spherical silicon product does not contain large particles larger than 10 microns.

[0021] It should be noted that the reaction conditions of the present invention are crucial, which will not only affect the in-situ synthesis of zinc molybdate particles and the morphology and particle size of the synthesized zinc molybdate particles, but also affect the bonding strength between the zinc molybdate particles and silica. In particular, the control of the reaction temperature is crucial. When the reaction temperature is too low, the zinc molybdate particles cannot be in-situ synthesized on the surface of spherical silica; when the reaction temperature is too high, the number of zinc molybdate particles will be small, and non-spherical zinc molybdate particles will be easily formed and mixed in the spherical silica.

[0022] The reaction temperature, time and pressure can be selected from any numerical range within the numerical range, and any specific numerical value within the numerical range. For example, the reaction temperature can be 130-150°C, 145-160°C or 165-180°C, or 130°C, 140°C, 150°C, 155°C, 160°C, 167°C, 175°C or 180°C.

[0023] At the same time, the soluble molybdate includes but is not limited to ammonium molybdate, sodium molybdate, potassium molybdate, etc., and the soluble zinc salt includes but is not limited to zinc sulfate, zinc nitrate, zinc chloride, etc., as long as the soluble molybdate can react with the zinc salt to form zinc molybdate and will not bring other negative effects on product performance.

[0024] Furthermore, the D50 of the spherical silica raw material used is 0.5-5 microns, the D50 of the spherical silicon obtained after coating is 0.6-6 microns, the conductivity is ≤100us / cm, the pH is 6-8, and the zinc molybdate content per unit area of ​​the spherical silica surface is 0.03-1g / m 2 , the size of the zinc molybdate particles is ≤400nm.

[0025] Furthermore, it also includes:

[0026] The material obtained after the reaction is filtered and washed; and / or

[0027] Drying the material obtained after the reaction; and / or

[0028] The materials obtained after the reaction are broken up and classified.

[0029] Furthermore, when the material obtained after the reaction is filtered, pure water is repeatedly used for rinsing during the filtering process until the conductivity of the material is ≤100us / cm; the drying temperature is 100-150°C.

[0030] Furthermore, it also includes:

[0031] Add spherical silica to water and stir evenly;

[0032] Then, add soluble molybdate and zinc salt aqueous solutions thereto and stir evenly;

[0033] Wherein, the concentration of the soluble molybdate aqueous solution is 1-8 mol / l, and the concentration of the soluble zinc salt aqueous solution is 1-8 mol / l.

[0034] The third aspect of the present invention further provides a modified spherical silicon for copper-clad laminates, the modified spherical silicon comprising modified spherical silicon dioxide and zinc molybdate particles in-situ dispersedly grown on the surface of silicon dioxide, wherein the structural formula of the surface group of the modified spherical silicon dioxide is as follows:

[0035]

[0036] Due to the increasing requirements of dielectric properties for copper-clad laminates, a large amount of resins with very low polarity are used, especially polyphenylene ether, a highly heat-resistant, highly reliable, low-polarity resin, but its compatibility with fillers is very poor. When the modified spherical silica of the present invention is used as a filler, the compatibility between the filler and the polyphenylene ether resin can be effectively improved, especially in a highly filled system, thereby improving the peel strength of the copper-clad laminate; at the same time, the hydroxyl content of the modified spherical silica is relatively low, thereby avoiding the high hydroxyl content in the electric field, which is easy to polarize and lead to an increase in dielectric loss, and thus it is beneficial to further reduce the dielectric loss of the spherical silica product.

[0037] More preferably, the hydroxyl content of the modified spherical silica is 0.1-10 / nm 2 .

[0038] Further preferably, the diameter of the modified spherical silica is less than 10 microns, and the D50 is 0.6 to 6 microns; and / or the zinc molybdate content per unit area on the surface of the modified spherical silica is 0.03-1 g / m 2 , the size of zinc molybdate particles is ≤400nm.

[0039] The fourth aspect of the present invention further provides a preparation process of any modifier as described in the third aspect, specifically comprising:

[0040] The modifier is contacted / mixed with the spheroidal silicon described in the first aspect of the present invention or the spheroidal silicon prepared by any process described in the second aspect in a reaction solvent to react and obtain modified spheroidal silicon; wherein the reaction conditions include: a reaction temperature of 25-120° C., a reaction time of 1-9 hours, an addition amount of the modifier of 0.2-3% of the total mass of the spheroidal silicon chemically coated with zinc molybdate particles, and the structural formula of the modifier is as follows:

[0041]

[0042] Furthermore, the reaction solvent is 2-hexanol. Alcohols with shorter chains, such as ethanol, have lower boiling points than 2-hexanol and cannot meet the temperature requirements of 120° C. or above, and have higher costs than alcohols with longer chains.

[0043] Furthermore, the method further comprises: filtering, drying or breaking up and classifying the modified spherical silica obtained by the reaction, or any combination thereof.

[0044] The fifth aspect of the present invention also provides a resin composition comprising a resin and a filler, wherein the filler comprises any spherical silica described in the first aspect of the present invention, or spherical silica prepared by any process described in the second aspect of the present invention, or any modified spherical silica described in the third aspect of the present invention, or modified spherical silica prepared by any preparation process described in the fourth aspect of the present invention.

[0045] Furthermore, the filling amount of spherical silica or modified spherical silica in the resin composition is 50-65%.

[0046] The sixth aspect of the present invention further provides a copper clad laminate, which is made of any resin composition described in the fifth aspect of the present invention.

[0047] Furthermore, the dielectric loss of the copper clad laminate made of the resin composition is 0.001-0.003, and the peel strength is 1.0-1.5 N / inch.

[0048] In summary, the technical solution provided by the present invention can achieve the following beneficial effects compared with the prior art:

[0049] (1) The present invention provides spherical silicon for copper-clad laminates, which is composed of spherical silicon dioxide and zinc molybdate particles in-situ dispersedly grown on the surface of the spherical silicon dioxide. In particular, the distribution of the zinc molybdate particles on the surface of the spherical silicon dioxide is optimized. When the spherical silicon is applied to copper-clad laminates, the filling amount of the filler can be effectively increased, and the wear of the drill bit during the drilling process of the copper-clad laminates can be reduced. In addition, the zinc molybdate particles are firmly bonded to the surface of the silicon dioxide and are not easy to fall off during subsequent applications.

[0050] (2) The present invention adopts a hydrothermal method and strictly controls its specific process parameters, thereby ensuring that highly dispersed zinc molybdate particles are directly synthesized in situ on the surface of spherical silicon dioxide, and controlling the morphology and particle size of the synthesized zinc molybdate particles, while preventing the zinc molybdate particles from falling off, thereby ensuring the application effect of the spherical silicon dioxide.

[0051] (3) The present invention also provides a modified spherical silica, which is further modified by using a specific modifier to further modify the spherical silica coated with zinc molybdate particles so as to graft new groups on the surface of spherical silica, thereby effectively improving the compatibility between the spherical silica filler and the polyphenylene ether resin and facilitating the improvement of the peel strength of the copper clad laminate. In addition, the hydroxyl content of the spherical silica can be effectively controlled to prevent the increase of dielectric loss caused by polarization of the hydroxyl group in the electric field, which is beneficial to further reduce the dielectric loss of the obtained spherical silica.

[0052] (4) The spherical silica or modified spherical silica of the present invention is used as a filler, mixed with a resin and then applied to a copper clad laminate. Compared with the prior art in which talcum powder is added to reduce drill wear during drilling, the dielectric loss of the copper clad laminate can also be effectively reduced and its PS strength can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 This is a scanning schematic diagram of the spherical silicon prepared in Example 1 of the present invention;

[0054] Figure 2 The XRD pattern of the spherical silicon prepared in Example 1 of the present invention;

[0055] Figure 3 This is a picture of the drill bit after drilling 1000 times in Example 1 of the present invention;

[0056] Figure 4 It is a scanning schematic diagram of spherical silica before coating;

[0057] Figure 5 This is a scanning schematic diagram of the direct physical mixing of spherical silicon dioxide and zinc molybdate in Comparative Example 1;

[0058] Figure 6 This is a picture of the drill bit in Comparative Example 1 after drilling 1000 times;

[0059] Figure 7 This is a scanning schematic diagram of the spherical silicon prepared in Example 2;

[0060] Figure 8 This is a picture of the drill bit after drilling 1000 times in Example 2;

[0061] Fig. 9 This is a picture of the drill bit after drilling 1000 times in Example 3;

[0062] Fig.10 This is a scanning schematic diagram of spherical silicon in Example 3;

[0063] Fig.11 is the infrared spectrum of the modifier used in Example 4;

[0064] Fig.12 is the infrared spectrum of the modified spherulitic silicon obtained in Example 4;

[0065] Fig.13 This is a picture of the drill bit after drilling 1000 times in Example 4;

[0066] Fig.14 It is a scanning schematic diagram of talcum powder in comparative example 5;

[0067] Fig.15 is the scanning spectrum of the spherical silicon obtained in Comparative Example 6;

[0068] Fig.16 is the scanning spectrum of the spherical silicon obtained in Comparative Example 7;

[0069] Fig.17 Schematic diagram of scanning of spherical silicon obtained in Example 5;

[0070] Fig.18 Schematic diagram of scanning of spherical silicon obtained in Example 6;

[0071] Fig.19 This is a picture of the drill bit in Example 6 after drilling 1000 times.

[0072] Test method:

[0073] 1. Hydroxyl test method: Test method for silanol content on the surface of fumed silica T / FSI 049-2020;

[0074] 2. Large particle test: Take 200g of powder and pass it through a 1000-mesh sieve, then take the material on the sieve and test it using a scanning electron microscope. DETAILED DESCRIPTION

[0075] In order to further understand the content of the present invention, the present invention is now described in detail in conjunction with specific embodiments.

[0076] Example 1

[0077] A preparation process of spherical silicon for copper-clad laminates of this embodiment includes:

[0078] Pure water was added to a polytetrafluoroethylene-lined hydrothermal reactor, followed by spherical silica (D50: 1.3 μm, SiO 2 Content: 99.82%), weight 10kg, then stirred at a stirring speed of 30HZ for 80 minutes;

[0079] Then add an aqueous solution of ammonium molybdate (6.2 mol / l) with a volume of 10 L, a stirring speed of 30 Hz, and a stirring time of 60 minutes;

[0080] Continue to add zinc sulfate aqueous solution (6.2 mol / l), volume 10L, then increase the reactor temperature (150°C), pressure (5 MPa), after reacting for 6 hours, release the contents of the reactor;

[0081] Release the material in the reactor and filter it using a filter press. Repeatedly rinse with pure water during the filtration process. Release the material when the conductivity of the material reaches ≤100us / cm.

[0082] The washed material is dried using a flash dryer at 130°C;

[0083] The dried material is broken up and classified using a fluidized bed airflow classifier to obtain spherical silicon material coated with zinc molybdate on the surface. Its indicators are as follows: zinc molybdate content per unit area: 0.08g / m 2 The size of the zinc molybdate coated on the surface is: 50-400nm, the conductivity of the spherical silicon is: 50us / cm, and the hydroxyl content is: 15 / nm 2 , D50 is 1.5 microns.

[0084] The scanning images and XRD patterns of the spherical silicon prepared in this example are shown in Figure 1 , Figure 2 As shown. Figure 4 The figure shows the spherical silica before coating. Its surface is relatively smooth. Figure 1 It can be seen that in this embodiment, after coating, granular substances are obviously generated on the surface of the spherical silicon dioxide. Figure 2 In the XRD spectrum, positions 32, 33, 34, 35, 48, 57, 63, 67, 68, and 69 correspond to the standard peaks of zinc molybdate, proving that zinc molybdate is in situ grown on the surface of spherical silica.

[0085] This embodiment also provides a resin composition, comprising the spherical silicon prepared in this embodiment and polyphenylene ether resin, wherein the filling amount of the spherical silicon is 60%. The resin composition is glued to glass cloth (2116, Chongqing International Composite Materials) by a glue machine (vertical glue machine, China Taiwan Yatai Metal Industry Co., Ltd.), the glue content is 56%, and the vacuum press (800T-12, Weidi Electromechanical Technology Co., Ltd.) is placed under a constant temperature of 280°C and a vacuum degree of 10 -3pa, press 15Mpa to make a prepreg, take 8 prepared prepregs and stack them together, put copper foil (35μm, Jiantao Chemical Group) on the top and bottom of the stacked prepreg, and put it in a vacuum press (Aist (Shanghai) Mechanical Technology Co., Ltd.), while the press is kept at 290℃ and the vacuum degree is 10 -3 pa, press pressure 16Mpa, made into copper clad laminate.

[0086] Use a drill to drill holes in the copper clad laminate and test the wear of the drill. Figure 3 The picture shown is after the drill bit drilled 1000 times. It can be seen from the picture that the drill bit is basically not worn after drilling 1000 times (the white part on the surface is very small). The peel strength of the copper clad laminate produced in this embodiment is 0.8N / inch.

[0087] Comparative Example 1

[0088] This comparative example directly forms spherical silica (D50: 1.3 μm, SiO 2 Content: 99.82%) and zinc molybdate were physically mixed, and the mixing mass ratio was the same as the mass ratio added in Example 1. After physical mixing, the conductivity of the spherical silicon product was 56us / cm, and the hydroxyl content was 28 / nm 2 , D50 is 1.5 microns.

[0089] The above mixture is used as filler (the scanned image of the filler is as follows Figure 5 As shown, it can be clearly seen that non-spherical zinc molybdate exists in the spherical silicon dioxide, and the size is greater than 800nm) and mixed with polyphenylene ether resin to make a resin composition and a copper clad laminate. The filling amount of the filler and the specific production process of the copper clad laminate are the same as in Example 1.

[0090] Use a drill to drill holes in the copper clad laminate and test the wear of the drill. Figure 6 The picture shown is after the drill bit drilled 1000 times. It can be seen from the picture that the physical mixing of spherical silica and zinc molybdate directly has a relatively weak effect on improving the wear of the drill bit during drilling, and there are more white parts on the surface of the drill bit after wear.

[0091] Example 2

[0092] The preparation process of spherical silicon for copper-clad laminate of this embodiment includes:

[0093] Pure water was added to a polytetrafluoroethylene-lined hydrothermal reactor, followed by spherical silica (D50: 1.2 μm, SiO 2 Content: 99.7%), weight 10kg, then stirred at a stirring speed of 10HZ for 120 minutes;

[0094] Then add an aqueous solution of ammonium molybdate (8 mol / l), volume 6 L, stirring speed 10 Hz, stirring time 120 minutes;

[0095] Continue to add zinc sulfate aqueous solution (8 mol / l), volume 6 L, then increase the reactor temperature (130 ° C), pressure (8 MPa), after reacting for 8 hours, release the materials in the reactor;

[0096] Release the material in the reactor and filter it using a filter press. Repeatedly rinse with pure water during the filtration process. Release the material when the conductivity of the material reaches ≤100us / cm.

[0097] The washed material is dried using a flash dryer at 150°C;

[0098] The dried material is broken up and classified using a fluidized bed airflow classifier to obtain a spherical silicon material (such as Figure 7 The indicators are as follows: zinc molybdate content per unit area: 0.04g / m 2 , conductivity: 35us / cm, hydroxyl content: 13 / nm 2 , D50 is 1.3 microns, and the size of the surface-coated zinc molybdate is 80 to 300 nm.

[0099] The spherical silicon prepared in this example was mixed with polyphenylene ether resin to prepare a resin composition (the filling amount of spherical silicon was 55%), and the resin composition was used to prepare a copper-clad laminate. The results showed that the use of the spherical silicon in this example as a filler can effectively improve the wear of the drill bit during the drilling of the copper-clad laminate (such as Figure 8 The picture shows the drill bit after drilling 1000 times), and the wear of the drill bit is relatively small; and the peel strength of the copper clad laminate produced in this embodiment is 0.9N / inch.

[0100] Example 3

[0101] The preparation process of spherical silicon for copper-clad laminate of this embodiment includes:

[0102] Pure water was added to a polytetrafluoroethylene-lined hydrothermal reactor, followed by spherical silica (D50: 0.5 μm, SiO 2 Content: 99.8%), weight 10kg, then stirred at a stirring speed of 40HZ for 10 minutes;

[0103] Then add an aqueous solution of ammonium molybdate (3 mol / l), volume 10 L, stirring speed 40 Hz, stirring time 10 minutes;

[0104] Continue to add zinc sulfate aqueous solution (3 mol / l), volume 10 L, then increase the reactor temperature (180°C), pressure (1 MPa), react for 3 hours and release the materials in the reactor;

[0105] Release the material in the reactor and filter it using a filter press. Repeatedly rinse with pure water during the filtration process. Release the material when the conductivity of the material reaches ≤100us / cm.

[0106] The washed material is dried using a flash dryer at 110°C;

[0107] The dried material is broken up and classified using a fluidized bed airflow classifier to obtain a spherical silicon material (such as Fig.10 The indicators are as follows: zinc molybdate content per unit area: 0.03g / m 2 , conductivity 30us / cm, hydroxyl content: 12 / nm 2 , D50 is 0.6 microns, and the size of the surface-coated zinc molybdate is 40-300nm.

[0108] The spherical silicon prepared in this example was mixed with polyphenylene ether resin to prepare a resin composition (the filling amount of spherical silicon was 60%), and the resin composition was used to prepare a copper-clad laminate. The results showed that the use of the spherical silicon in this example as a filler can effectively improve the drill wear during the drilling of the copper-clad laminate. The drill wear picture after drilling 1000 times is as shown in the figure. Fig. 9 As shown, the peel strength of the copper clad laminate produced in this embodiment is 0.7N / inch.

[0109] Example 4

[0110] This example is based on the spherical silicon prepared in Example 1, and further modified. The structural formula of the modifier used is:

[0111]

[0112] One of the preparation processes of the modifier is as follows:

[0113] 1000 parts by mass of CH 3 CH 2 CH 2 SiCl 3 With 1000 parts by mass of Cl 2 Under light conditions and with the catalyst AlCl 3 The reaction was carried out to obtain ClCH 2 CH 2 CH 2 SiCl 3 ;

[0114] 1000 parts by mass of 2,6-dimethylphenol and 1000 parts by mass of ClCH 2 CH 2 CH 2 SiCl 3 Reaction, obtained

[0115]

[0116] Utilize 3000 weight parts of methanol and 1000 weight parts of the above-mentioned product to carry out alcoholysis reaction, namely obtain

[0117]

[0118] The structure of synthesized organic compounds can be identified by Fourier transform infrared spectroscopy (FT-IR) spectra, such as Fig.11 As shown, at 1377.48cm -1 and 2918.89cm -1 The absorption peak at 1602.64 cm is attributed to the bending vibration of the CH bond of the methyl group on the benzene ring. -1 and 1467.56cm -1 The absorption peak at 1304.81cm is attributed to the stretching vibration peak of the carbon-carbon bond on the benzene ring skeleton. -1 、1184.99cm -1 and 1018.94cm -1 The absorption peak that appears is attributed to the stretching vibration of the COC bond on the polyphenylene ether skeleton, 1190 cm -1 、2861.12cm -1 Si-O-CH 3 Extension vibration, 1602.64cm -1 、1494.71cm -1 for Stretching vibration, 2098.00cm -1 -CH 2 -CH 2 -CH 2 -Stretching vibration of Si bond, 907.65 cm -1 , 855.91cm -1 , 829.09cm -1 , 728.27cm -1 , 694.32cm -1 is the stretching vibration on the H plane of the benzene ring, 958.80 cm -1 It is the stretching vibration in the H plane of the benzene ring. 1304.81cm -1 is the stretching vibration of the benzene ring skeleton, 3024.68cm -1It is the stretching vibration of H on the benzene ring. From the above data, it can be known that the synthetic substance is a modifier of the above structure.

[0119] The manufacturing process of the modified spheroidal silicon in this embodiment specifically includes:

[0120] a. Add the modifier according to 0.2-3% of the mass of spherical silicon and the zinc molybdate-coated spherical silicon powder into the reactor, and add 2-hexanol at the same time, 2-hexanol submerges the materials, the temperature of the reactor is 25-120° C., the reaction time is 1-9 hours, and specifically in this embodiment, the amount of the modifier added is 1.5% of the mass of the zinc molybdate-coated spherical silicon powder, the reaction temperature is 80° C., and the reaction time is 5 hours;

[0121] b. The slurry after the reaction is discharged from the reactor, and then filtered, and spray-dried by a spray drying device at a drying temperature of 150° C. At the same time, the vaporized 2-hexanol is collected;

[0122] c. Finally, the spray-dried material is broken up using a fluidized bed airflow pulverizer to obtain modified spherical silicon.

[0123] The structure of the modified spherulite was identified by Fourier transform infrared spectroscopy (FT-IR). Fig.12 As shown, at 1377.48cm -1 and 2918.89cm -1 The absorption peak at 1602.64 cm is attributed to the bending vibration of the CH bond of the methyl group on the benzene ring. -1 and 1467.56cm -1 The absorption peaks at 1304.81cm-1, 1184.99cm-1 and 1018.94cm-1 are attributed to the stretching vibration of the carbon-carbon bond on the benzene ring skeleton, the absorption peaks at 2861.12cm-1 are attributed to the stretching vibration of the COC bond on the polyphenylene ether skeleton, and the absorption peaks at 1304.81cm-1, 1184.99cm-1 and 1018.94cm-1 are attributed to the stretching vibration of the COC bond on the polyphenylene ether skeleton. -1 Si-O-CH 3 The stretching vibration peak of 1602.64cm disappears, which is mainly due to the reaction between silane and the hydroxyl group on the surface of the spherical silicon material. -1 、1494.71cm -1 for Stretching vibration, 2098.00cm -1 The stretching vibration of -CH2-CH2-CH2-Si bond, 907.65cm -1 , 855.91cm -1 , 829.09cm -1 , 728.27cm -1 , 694.32cm -1 The stretching vibration of the H plane on the benzene ring is 958.80cm -1It is the stretching vibration in the H plane of the benzene ring. 1304.81cm -1 is the stretching vibration of the benzene ring skeleton, 3024.68cm -1 It is the stretching vibration of H on the benzene ring, and the new addition is 1010.20 cm -1 It is a chemical bond of Si-O-Si, which shows that silane reacts with the hydroxyl groups on the surface of spherical silicon material to generate a new structural formula

[0124]

[0125] That is, the modified spherical silicon obtained in this embodiment includes modified spherical silicon dioxide and zinc molybdate particles dispersed and grown in situ on the surface of silicon dioxide. After the modification, the modifier reacts with the hydroxyl groups on the surface of the spherical silicon dioxide to form

[0126]

[0127] The modified spheroidal silica prepared in this example was mixed with polyphenylene ether resin to prepare a resin composition, and the resin composition was used to prepare a copper-clad laminate, wherein the filling amount of the modified spheroidal silica and the specific preparation process of the copper-clad laminate were the same as those in Example 1. The results showed that the modified spheroidal silica in this example can not only effectively improve the drill wear during the drilling of the copper-clad laminate, but also the drill wear picture after drilling 1000 times is as shown in the figure. Fig.13 As shown, it can also effectively improve the compatibility between the filler and the polyphenylene ether resin and increase the peel strength of the copper clad laminate. The peel strength is 1.4N / inch, and the hydroxyl content of the surface of the modified spherical silicon is 3.3 / nm. 2 .

[0128] Comparative Example 2

[0129] On the basis of Example 4, the coupling agent was changed to vinyl silane, and the rest remained unchanged. The obtained modified spherical silica was mixed with resin and used to make a copper clad laminate. The peel strength of the obtained copper clad laminate was: 0.9N / inch (vinyl silane has a certain effect of improving the peel strength).

[0130] Comparative Example 3

[0131] On the basis of Example 4, the coupling agent was replaced with epoxy silane, and the rest remained unchanged. The obtained modified spherical silica was mixed with resin and used to make a copper clad laminate. The peel strength of the obtained copper clad laminate was 0.72 N / inch.

[0132] Comparative Example 4

[0133] On the basis of Example 4, the coupling agent was replaced with aminosilane, and the rest remained unchanged. The obtained modified spherical silica was mixed with resin and used to prepare a copper clad laminate. The peel strength of the obtained copper clad laminate was 0.74 N / inch.

[0134] Comparative Example 5

[0135] On the basis of Example 4, the spherical silicon dioxide was replaced with talcum powder of the same particle size. Since the talcum powder has a distinct lamellar structure (such as Fig.14 As shown), the talcum powder material coated with zinc molybdate becomes very viscous and cannot be used at all.

[0136] Comparative Example 6

[0137] The main difference between this comparative example 1 and example 1 is that the reaction temperature of the hydrothermal reaction is 120°C. Fig.15 As shown, zinc molybdate is basically not generated on the surface of spherical silicon.

[0138] Comparative Example 7

[0139] The main difference between this comparative example 1 and example 1 is that the reaction temperature of the hydrothermal reaction is 185°C. Fig.16 As shown, the temperature is too high, less zinc molybdate is formed on the surface of the spherical silicon, and non-spherical zinc molybdate particles are formed and mixed in the spherical silicon.

[0140] Example 5

[0141] This example is based on the spherical silicon prepared in Example 2, and further modified. The modifier used is the same as that in Example 4. The modification process of this example is basically the same as that in Example 4. The main difference is that in this example, the amount of ammonium molybdate and zinc sulfate added in the preparation of spherical silicon is 6.2 mol / l, and the volume is 20 L. The zinc molybdate content per unit area of ​​the modified spherical silicon obtained in this example is: 1.0 g / m 2 , reaction temperature is 150°C, and reaction time is 1 hour.

[0142] Conclusion: The hydroxyl content of the surface of the modified spherical silica is 7 / nm 2 The peel strength of the copper clad laminate is 1.1N / inch, but the excessive zinc molybdate content will cause the PS to be slightly lower, as shown in the SEM image in Figure 17.

[0143] Example 6

[0144] This example is based on the spherical silicon prepared in Example 3, and further modified. The modifier used is the same as that in Example 4. The modification process of this example is basically the same as that in Example 4. The main difference is that in this example, the amount of ammonium molybdate and zinc sulfate added in the preparation of spherical silicon is 6.2 mol / l, and the volume is 5 L. The content of zinc molybdate per unit area on the surface of the modified spherical silicon dioxide obtained in this example is 0.03 g / m 2 , reaction temperature is 150°C, and reaction time is 6 hours.

[0145] The test results are as follows: The hydroxyl content of the surface of the modified spherical silica is 4 / nm2 The peel strength of the copper clad laminate is 1.3N / inch, and the SEM Fig.18 As shown in Figure 2, the wear of the drill bit after drilling 1000 times is as follows: Fig.19 As shown, the surface wear is small.

[0146] Example 7

[0147] The preparation process of the modified spheroidal silica in this embodiment is basically the same as that in Example 4, the main difference is that the amount of the modifier added in this embodiment accounts for 0.5% of the mass of the zinc molybdate-coated spheroidal silica powder, the reaction temperature is 150° C., and the reaction time is 1 hour.

[0148] The test results are as follows: The hydroxyl content of the surface of the modified spherical silica is 8 / nm 2 , the peel strength of the copper clad laminate is 1.0N / inch.

[0149] Example 8

[0150] This example is based on the spherical silicon prepared in Example 3, and further modified. The modifier and modification process used are basically the same as those in Example 4. The main difference is that the amount of the modifier added in this example accounts for 3% of the mass of the zinc molybdate-coated spherical silicon powder, the reaction temperature is 150°C, and the reaction time is 6 hours.

[0151] The test results are as follows: The hydroxyl content of the surface of the modified spherical silica is 2 / nm 2 , the peel strength of the copper clad laminate is 15N / inch.

[0152] In summary, the present invention directly synthesizes zinc molybdate in situ on the surface of spherical silicon dioxide by a hydrothermal method, and especially optimizes and controls the reaction temperature, pressure and time, so that not only the structural morphology of the obtained spherical silicon and the size of the zinc molybdate particles can be effectively controlled, and the drill wear during drilling of the copper clad laminate can be effectively improved, and the drill wear rate can be reduced from the existing 5% to 2%; at the same time, the binding firmness between the zinc molybdate particles and the silicon dioxide can be effectively guaranteed to prevent falling off. By further modifying the obtained spherical silicon, not only can its compatibility with the resin be effectively improved, and the peel strength of the copper clad laminate be increased, but also the dielectric loss of the copper clad laminate can be further reduced.

Claims

1. A spherical silicon for copper clad laminate, characterized in that: The spherical silicon is composed of spherical silicon dioxide and zinc molybdate particles dispersed and grown in situ on the surface of the spherical silicon dioxide. The diameter of the spherical silicon dioxide is less than 10 microns, the D50 is 0.6 to 6 microns, and the zinc molybdate content per unit area on the surface of the spherical silicon dioxide is 0.03-1g / m 2 , the size of the zinc molybdate particles is ≤400nm.

2. The spherical silicon for copper clad laminate according to claim 1, characterized in that: The pH of the spherical silica is 6-8, the conductivity is ≤100us / cm, and the D50 of the spherical silicon dioxide is 0.5-5 microns.

3. A process for preparing spherical silicon for copper-clad laminates, characterized in that: include: contacting / mixing spherical silica with soluble molybdate and zinc salt in an aqueous reaction system; The soluble molybdate and the zinc salt are reacted in situ on the surface of the spherical silicon dioxide to form spherical silicon dispersed and chemically coated with zinc molybdate particles; The soluble molybdate and the zinc salt are reacted in situ on the surface of spherical silica, and the reaction conditions include: reaction temperature of 130-180° C., reaction pressure of 1-8 MPa, and reaction time of 1-8 hours.

4. The process for preparing spherical silicon for copper-clad laminate according to claim 3, characterized in that: The D50 of the spherical silica raw material used is 0.5-5 microns, the D50 of the spherical silicon obtained after coating is 0.6-6 microns, the conductivity is ≤100us / cm, the pH is 6-8, and the zinc molybdate content per unit area of ​​the spherical silica surface is 0.03-1g / m 2 , the size of the zinc molybdate particles is ≤400nm.

5. The process for preparing spherical silicon for copper-clad laminate according to claim 3 or 4, characterized in that: Also includes: The material obtained after the reaction is filtered and washed; and / or Drying the material obtained after the reaction; and / or The materials obtained after the reaction are broken up and classified.

6. The process for preparing spherical silicon for copper-clad laminate according to claim 5, characterized in that: When the material obtained after the reaction is filtered, pure water is repeatedly used for rinsing during the filtering process until the conductivity of the material is ≤100us / cm; and / or the drying temperature is 100-150°C.

7. A modified spherical silicon for copper clad laminate, characterized in that: The modified spherical silicon comprises modified spherical silicon dioxide and zinc molybdate particles dispersedly grown in situ on the surface of the silicon dioxide, wherein the structural formula of the surface group of the modified spherical silicon dioxide is as follows:

8. The modified spheroidal silicon for copper-clad laminate according to claim 7, characterized in that: The hydroxyl content of the modified spherical silica is 0.1-10 / nm 2 ; and / or the diameter of the modified spherical silicon is less than 10 microns, and D50 is 0.6 to 6 microns; and / or the zinc molybdate content per unit area on the surface of the modified spherical silicon dioxide is 0.03-1g / m 2 , the size of zinc molybdate particles is ≤400nm.

9. A process for preparing modified spheroidal silicon for copper-clad laminates as claimed in claim 7 or 8, characterized in that: include: The modifier is contacted / mixed with the spheroidal silicon prepared by the process described in claim 1 or 2 or any one of claims 3 to 6 in a reaction solvent to react and obtain modified spheroidal silicon; wherein the reaction conditions include: a reaction temperature of 25-120° C., a reaction time of 1-9 hours, an addition amount of the modifier of 0.2-3% of the total mass of the spheroidal silicon chemically coated with zinc molybdate particles, and the structural formula of the modifier is as follows:

10. A resin composition comprising a resin and a filler, characterized in that: The filler includes spherical silica prepared by the preparation process described in claim 1 or 2 or any one of claims 3-6, or modified spherical silica prepared by the preparation process described in claim 7 or 8 or claim 9.

11. The resin composition according to claim 10, characterized in that The filling amount of the spherical silica or modified spherical silica in the resin composition is 50-65%.

12. A copper clad laminate, characterized in that: The copper clad laminate is made of the resin composition according to claim 10 or 11, and has a dielectric loss of 0.001-0.003 and a peel strength of 1.0-1.5 N / inch.

Citation Information

Cited By

  • Copper clad laminate, resin composition for copper clad laminate, and spherical silicon and preparation method therefor

    WO2026103702A1